STUDY OF PSYCHOSOCIAL RISK FACTORS ASSOCIATED WITH COVID-19 AND ITS IMPACT ON THE HEALTH COMPANY SEGURILAB M&S GROUP - SALEM, SOFÍA ELENA ALARCÓN (South Eastern European Journal of Public Health, 2024)
This article addresses the author's interest in the impact on occupational health, particularly the psychosocial implications, that the pandemic has had on healthcare workers, specifically laboratory workers. It analyzes conceptual aspects from both national and international perspectives, including insights from international organizations and European studies. Conceptually framing the issue, COVID-19 is situated as a factor associated with psychosocial morbidity among laboratory workers, based on the perceptions of 40 workers. Factors associated with psychosocial disorders such as stress are identified, with an unexpected growth leading to organizational hypertrophy and subsequent mandatory staff expansion. This resulted in increased work hours and responsibility, leading to a sense of instability. Methodologically, the study describes and explores the phenomenon, considering the entire workforce at the Quito Headquarters. Data collection was done through a perception-based scaling instrument. Regarding the results, a vast majority acknowledged experiencing work-related stress, with "information" identified as one of the causes. Assuming responsibility and a high workload were also stress factors. Organizational growth and the influx of new personnel contributed to a sense of job instability, leading to continuous organizational changes that affected working conditions. Recommendations include adapting the current protocols for psychosocial disorders used by the Ministry of Labor to incorporate COVID-19 experiences. Continuation of research in this area is also proposed to establish a solid line of investigation in the field of occupational psychosociology.